NON-FUNGIBLE TOKENS: AN ARGUMENT FOR THE OWNERSHIP OF DIGITAL PROPERTY? - Alessandro, Matteo (International Journal of Law in Changing World, 2023)
The paper examines the concept of ownership and its potential application to digital assets, particularly Non-Fungible Tokens (“NFTs”). Technological advancements which allow the creation, storage, and sale of unique digital assets in a purely digital manner have raised many questions about the concept of ‘digital ownership’. However, the legal frameworks regulating the ownership, sale, and legal classification of digital assets have not evolved at the same pace as technology. This leads to legal uncertainty in the digital landscape, and weakened protection for the users of this technology, particularly in the European Union (“EU”). Although the concept of digital property has been discussed theoretically, practical recommendations for the implementation of this concept are still scarce. This paper discusses the concept of digital property after providing a contextual understanding of NFTs and the technology behind them. The paper aims to provide practical solutions based on analysis of possible approaches and an analysis of the current legal landscape. The paper will first provide an overview of the use-cases of NFTs, as well as their characteristics. A comparative legal analysis is then applied to examine the legal classification of NFTs, and the ownership of digital property in jurisdictions across the globe. Following this, the potential implications of the lack of proper regulation will be discussed through a conceptual legal analysis. A theoretical exercise will then be conducted to examine the potential of NFTs to attract property rights, based on theories proposed through literature. Finally, recommendations are proposed for a harmonised EU-level framework for the legal classification of NFTs, and for the concept of digital property.